Carbon Sequestration in the Standing Trees at the Amrai Park of Sangli City (Maharashtra – 416 416) - Kulkarni, Narendra Anant (Plantae Scientia, 2018)
Plants are known to absorb the atmospheric carbon by photosynthesis. This absorbed carbon is stored in various organic forms and helps to produce the biomass. The absorption of the atmospheric carbon is depend on the structure and life form of the plants. Trees dominate this process. Greater and taller is the size of the tree more is the amount of carbon fixed. Hence trees are the major plant forms to absorb maximum atmospheric carbon and biomass production. Thus, the present investigation was carried out to calculate the carbon sequestration of 22 standing tree species in Amrai Park of Sangli city. The biomass and total organic carbon of standing trees is estimated by the non destructive method. The population of Swieteniamahagoni(C) Jacq.is more in the campus and it sequestrates the 77509.25 lbs carbon/year.